Paradigm in Islamic Education (Islamic Education Thought Analysis Study) - Dewi, Arini Kusuma; Afifah, Sekar Rana; Hidayatullah, Ahmad Fauzan (Khatulistiwa, 2021)
Paradigm is a person's view of himself and the environment that can influence thinking, wrong, and behavior. Where this paradigm is closely related to the principles that determine the various kinds of human views of the world. The instruction is intended to make a climate in the educating and learning measure with the goal that understudies are dynamic in building up their capability to have character, otherworldly information, discretion, insight, and respectable ethics. For this reason, Islamic education can create human dignity, noble character and noble character. Islamic education supports creating warmth to change and augmenting his potential in doing his obligations as abid and caliph with  duty and currently improving the quality of Islamic education is being discussed by many people related to government efforts to align Islamic education with general education at all levels. Education. This is stipulated in Law No. 20/2003 on the national education system which is willing to declare education as one of the national education sub-systems that has the right to receive equal treatment and equal to general education